2019
DOI: 10.18632/aging.102378
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA HULC promotes hepatocellular carcinoma progression

Abstract: Long noncoding RNAs (lncRNAs) are overexpressed in many types of cancers, suggesting they may promote tumorigenesis. The lncRNA “highly upregulated in liver cancer” (HULC) promotes hepatocellular carcinoma (HCC) by mechanisms that are not fully understood. In the present study, we showed that HULC is overexpressed in HCC tissues, which correlates with an unfavorable prognosis in HCC patients. We also found that HULC promotes the proliferation, migration, and invasion of HCC cells in vitro, and xenograft tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…SNHG11 promotes proliferation and metastasis by targeting the Hippo pathway in colorectal cancer and may act as diagnostic markers for the detection of pancreatic cancer and prostate cancer. [11][12][13] Recent studies have shown that lncRNA regulates cell proliferation, apoptosis, metastasis, invasion, angiogenesis, lipid metabolism, EMT, and many other processes, and has an impact on tumor size, TNM grade, postoperative survival, and prognosis of HCC. 8,[14][15][16] Bioinformatics analysis and luciferase reporter assay found that the binding site of SNHG11 is miR-184 and miR-184 directly targets AGO2.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG11 promotes proliferation and metastasis by targeting the Hippo pathway in colorectal cancer and may act as diagnostic markers for the detection of pancreatic cancer and prostate cancer. [11][12][13] Recent studies have shown that lncRNA regulates cell proliferation, apoptosis, metastasis, invasion, angiogenesis, lipid metabolism, EMT, and many other processes, and has an impact on tumor size, TNM grade, postoperative survival, and prognosis of HCC. 8,[14][15][16] Bioinformatics analysis and luciferase reporter assay found that the binding site of SNHG11 is miR-184 and miR-184 directly targets AGO2.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are a class of ncRNAs with more than 200 nucleotides (nt) in length (Ponting et al, 2009). Increasing evidences have demonstrated that lncRNAs are implicated in almost all physiological and pathological processes, including cancers (Esposito et al, 2019;Sweta et al, 2019;Zhang et al, 2019). Many lncRNAs are revealed to be dysregulated in various cancers, including HCC (Li et al, 2017;Berger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA highly upregulated in liver cancer (HULC) is closely related to liver diseases [93,94], which play a key role in liver fibrosis [67]. HULC expression levels were increased in liver tissues from nonalcoholic fatty liver disease rats [67].…”
Section: Hulcmentioning
confidence: 99%